Different Products of the Reduction of (N), C, N‐Chelated Antimony(III) Compounds: Competitive Formation of Monomeric Stibinidenes versus 1H‐2, 1‐Benzazastiboles. Issue 10 (16th January 2017) - Vránová, Iva; Alonso, Mercedes; Jambor, Roman; Růžička, Aleš; Turek, Jan; Dostál, Libor
Abstract: The reduction of N, C, N‐chelated antimony(III) chlorides [C6 H3 ‐2, 6‐(CH=NR)2 ]SbCl2 (R=Ph (1 ), t Bu (2 ), Dip (3 ); Dip=2, 6‐ i Pr2 C6 H3 ) with an appropriate amount of KC8 or Li[AlH4 ] resulted in the formation of rare examples of monomeric stibinidenes [C6 H3 ‐2, 6‐(CH=NR)2 ]Sb (R=Ph (4 ), t Bu (5 ), Dip (6 )). Similarly, the reduction of compounds1 or2 by two equivalents of K[B( s Bu)3 H] led to the stibinidenes4 and5 . In contrast, the analogous reaction of compound3 resulted in the formation of an unprecedented stibinidene [C6 H3 ‐2‐(CH=NR)‐6‐(CH2 NHR)]Sb (7 ) (R=Dip), in which the hydrogen atoms that come from the K[B( s Bu)3 H] are incorporated into the ligand backbone. To gain further insight into this intriguing reactivity with K[B( s Bu)3 H] and to assess the influence of the substitution at both the antimony atom and pendant substituents, we prepared compounds [C6 H3 ‐2‐(CH=NDip)]Sb(Ph)Cl (8 ) and [C6 H2 ‐2‐(CH=NDip)‐4, 6‐( t Bu)2 ]SbCl2 (9 ). The treatment of compound8 with K[B( s Bu)3 H] smoothly led to the 1‐Ph‐2‐Dip‐1 H ‐2, 1‐benzazastibole (11 ), whereas the reaction of compound9 with K[B( s Bu)3 H] resulted in either t Bu‐substituted 1‐Cl‐2‐Dip‐1 H ‐2, 1‐benzazastibole (13 ) or the formation of unprecedented Sb−Sb dimer bis(2‐Dip‐1 H ‐2, 1‐benzazastibole) (12 ) depending on the reaction stoichiometry. The miscellaneous reactivity of antimony(III) precursors with reducing agents together with the structure and bonding of the resulting products has also been investigated from a theoretical point of view. Abstract : Where to be reduced? The reduction of a set of (N, )C, N‐chelated antimony(III) compounds leads to either rare examples of monomeric stibinidenes or unprecedented 1 H ‐2, 1‐benzazastiboles depending on the reducing agents and ligand structure. This means that the substrate is reduced either at the antimony atom or imino functionality of the ligand backbone.